Effect of AlN addition on the reaction sintering of Al2TiO5 composites fabricated by spark plasma sintering - Mettaya Kitiwan; Duangduen Atong; Fumio Endo; Takashi Goto (My University, 2023)
Fully dense Al2TiO5–Al2O3–TiN (ATN) composites were fabricated by reactive sintering using spark plasma sintering at 1400°C for 5 min under 100 MPa in vacuum. An equimolar ratio of Al2O3:TiO2 was used as the starting powder, while the addition of 0–36 mol% AlN was investigated. The thermodynamic calculation indicates that the initial reaction was that of TiO2 and AlN, forming TiN and Al2O3, and then the remaining TiO2 reacted with Al2O3 to produce Al2TiO5. With the increase in AlN precursor, Al2TiO5 gradually decreased, while Al2O3 and TiN increased. The lattice parameters of Al2TiO5 were enlarged with AlN addition, implying the incorporation of N atoms in the Al2TiO5 unit cell. The addition of AlN effectively produced fully densified bodies with small grain size, and microcrack-free, which therefore enhanced the mechanical properties of ATN composites. At 36 mol% AlN addition, the composite shows Vickers hardness and fracture toughness of 16.26 ± 1.61 GPa and 5.20 ± 0.46 MPa.m1/2, respectively.
Keywords: Spark Plasma Sintering; Vickers hardness test; Advanced ceramic materials synthesis